Mass-dependent behaviour and the starvation-predation risk trade-off in passerine birds - MacLeod, R (2003)
For any individual to survive and reproduce it needs to gain sufficient energy to avoid starvation and while doing so avoid being killed by a predator. For birds, the massdependent predation risk hypothesis predicts that, because increased mass is expected to reduce maximum flight performance when escaping from predators, the starvationpredation risk trade-off will be mass-dependent. This thesis carried out a series of five studies to test specific theoretical predictions of this general hypothesis. The first study used data on the blackbird Turdus merula to model, for the first time for any species, how mass changes diurnally and seasonally over the whole year. The results showed that both seasonal and diurnal mass change were regulated as predicted by mass-dependent predation risk. The next three experimental studies used specially designed automated weighing and identification systems to investigate how wild great tits Parus major deal with mass-dependent predation risk. Perceived predation risk was manipulating using model sparrowhawks and the results showed, for the first time, that birds are capable of changing their diurnal body mass gain strategy in response to heightened predation risk. Then the effect of diurnal mass gain on flight performance was examined, no significant effects could be shown but the experiment demonstrated that this result, and previous similar results, are due to insufficient sample size rather than the absence of an effect. The final experiment investigated the effect of capture, by humans, on the perception of risk. Birds increased mass in response to capture consistent with the event being perceived as an interruption to foraging that increased starvation risk. Finally, a study of the house sparrow Passer domesticus showed that they appear to be responding to mass-dependent predation risk in a way that makes them particularly vulnerable to any decrease in the predictability of their food supply. The results suggest that mass-dependent predation risk may be the mechanism that has driven recent dramatic house sparrow declines.